2017
DOI: 10.30788/revcolreh.v14.n1.2015.24
|View full text |Cite
|
Sign up to set email alerts
|

Tendencias De La Investigación En Fonoaudiología: El Caso De La Universidad De Sucre

Abstract: El presente estudio tiene como objetivo realizar un análisis bibliométrico de la producción investigativa en los últimos nueve años (2005-2013) del programa de Fonoaudiología de la Universidad de Sucre, con la finalidad de conocer la situación actual de la investigación. Para ello, fueron analizados un total de 47 tesis y 28 monografías del repositorio de tesis de la biblioteca de la institución, sistematizados en una base de datos delimitada en las áreas de lenguaje, habla y audición. Para el análisis de esta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
1
0
1
Order By: Relevance
“…Las áreas tradicionales de la Fonoaudiología (Audición, Lenguaje y Voz) y las poblaciones de adultos y niños continúan siendo privilegiadas en la investigación. Ello coincide por lo reportado en estudios previos (Lander & Castro-Gómez, 2000;Montes et al, 2017;Puyuelo et al, 2010). Sin embargo, se evidencia un creciente interés por nuevas áreas que se han desarrollado como Deglución -Terapia miofuncional (Mendoza & Planells, 2018).…”
Section: Discussionunclassified
“…Las áreas tradicionales de la Fonoaudiología (Audición, Lenguaje y Voz) y las poblaciones de adultos y niños continúan siendo privilegiadas en la investigación. Ello coincide por lo reportado en estudios previos (Lander & Castro-Gómez, 2000;Montes et al, 2017;Puyuelo et al, 2010). Sin embargo, se evidencia un creciente interés por nuevas áreas que se han desarrollado como Deglución -Terapia miofuncional (Mendoza & Planells, 2018).…”
Section: Discussionunclassified
“…Other studies have reported that the highest percentages of research in speech language pathology with children are focused on the pathologization of childhood, as opposed to the premise of recognizing performance based on diversity. 26,27 The ambiguity in the conceptions of inclusive education and disability and in the research approach to the disorder may be the result of a traditional training in speech-language therapy based on rehabilitation with a standardizing vocation that seeks to calculate the deficiencies in language, hearing, speech and oral pharyngeal function; to discipline the tongue; and to establish truths about pathologized subjects. 28 Therefore, it is possible that some practices inherited from special education, segregation, integration and even from the traditional health paradigm still persist in some educational establishments.…”
Section: An Identity Problemmentioning
confidence: 99%